ANALISIS KEBUTUHAN PEMBELAJARAN BAHASA INGGRIS BERBASIS MULTIMODAL EKOLINGUISTIK DI UNIVERSITAS TANGERANG RAYA: English - Adiyan, Fidiatul; Ramadhani, Siffa Annisa Fitri; Hidantikarnillah, Vicky; Kuswiyanti, Tanti Sri; Fahmi, Muhammad Rizal Fahmi; Reynardi, Adam (Kopertis Region IV Jabar and Banten, 2026)
Abstract Language teaching in higher education is increasingly required to respond to global challenges, including environmental sustainability and the growing role of multimodality in literacy practices. This mini research aims to analyse students’ learning needs and lecturers’ perspectives on language instruction that integrates multimodal approaches and ecolinguistics perspectives. The study employed a qualitative descriptive approach using a needs analysis design. Data were collected through student questionnaires, in depth interviews with reading course lectures, and an analysis of teaching materials entitled Ecological Awareness in Modern Society. The findings indicate that students require language learning materials that address environmental issues and are presented through multiple modes, such as texts, visuals, and digital media, to enhance comprehension and engagement. Lecturers perceive that multimodal ecolinguistics based instruction can foster students’ critical literacy, ecological awareness, and language skills, although challenges remain in terms of material availability and instructional readiness. This study suggests the development of multimodal ecolinguistics based language learning materials as an innovative strategy to support contextual and sustainable language education in higher education. Keywords: ecolinguistics, multimodality, needs analysis